Reproctive and post-reproductive hormone levels in the lizard Sceloporus virgatus - Abelí., Allison J. (Instituto de Ecología, A.C., 1998)
Plasma leveis of six hormones (estradiol, progestsrone, testosterona, dihydrotestosterone, androstenediona, and corticosterons) were obtainad for males and femalea of Sceloporus virgatus (Phrynosomatidae) during and after the seasonal peak of mating activity. Seasonal variation in hormone levels was found. Females had higher corticosterone levels in August (well after oviposition) than in April (soon after emergance), but male corticosterona levels were lowest in August. Seasonal variation in basal corticosterone levels may reflect between-sex differences in the time of peak physiological stress. Male androgen levels peaked in April and May, coinciding with the peak of mating activity. Ventral coloration is exhibited during the social displays of many phrynosomatid lizards. Androganic influences on ventral coloration have been documentad in some lizards. Males and famales of S. virgatus have a greatly reduced amount and intensity of blue ventral coloration relativo to most other specíes in the genus. Variation in the size and color intensity of the blue ventral throat patch in males was not asociated with vanation in male hormone levels. Male peak testosterone levels in S. vigratus were comparable to those reported for other Scelopurus species with larger and brighter blue patches